Causes of Burnout in Elementary School Teachers - Afsan Nurrizki; Yunita Faela Nisa; Abdul Mujib (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Burnout among elementary school teachers is a significant issue that affects both the quality of education and the mental health of teachers. This study aims to identify the contributing factors to teacher burnout in elementary schools based on recent academic literature. A systematic literature review method was employed, analyzing both national and international journal articles. The findings indicate that excessive workload, emotional demands, lack of social support, and low professional recognition are the main causes of burnout. These results contribute to the development of targeted intervention strategies to enhance teacher well-being.